The masjid in modernity: Form, space and syntax - Jahn Kassim, Puteri Shireen; Mohd Nawawi, Norwina; Hamat, Sufian (MPH Group Printing (M) Sdn Bhd, 2016)
The chapter explores the formation of modern masjid in form and space syntax to unravel the link to tradition through the spiritual axis of hortizontality in unison with world ummah and verticality with the one Almighty Allah